Potencialidades de nanocristais semicondutores à base de zinco: controle da composição e da arquitetura morfológica através da abordagem de síntese - Santana, Genelane Cruz (2017)
The preparation of semiconductor nanocrystals (SNC) has been reported as the research foccus in several works owing to the optical and luminescent properties as well as the broad fields of application. In the first stage of this work, 2-mercaptoethanol-capped ZnS nanocrystals were prepared and characterized. The resulting nanocrystals were incorporated into a pre-formed polyurethane matrix playing the role of polyol-type monomer. In the second stage,the ZnS nanocrystals were doped with Mn2+ cations, considering that this strategy may improve the optical properties of the nanocrystals. In this study, it was observed that the changes in experimental parameters may allow the controlled formation of ZnO instead of ZnS, introducing a new route to ZnO obtainment. Concentration values of Mn2+ were lower than 1 %. Moreover, a study was carried out in order to clarify the structure-property relation, observing that the substitution of Zn2+ ions by Mn2+ ones may influence the optical properties of ZnO. From characterization data, the formation of ZnO was confirmed and it became clear that dissolving or notpreviously the capping agent in water was the key factor for the formation of ZnO instead of ZnS.Since small dopant concentrations lead to interesting results for ZnO, the same conditions were used to study the doping of ZnS in the third stage. This lead, however, to self-assembly of nanocrystals into nanowires after the doping process. Self-assembly did not cause changes in the absorption energies according to UV/visible spectra.This was the case even when the dopant concentration in the ZnS nanocrystals increased, as analyzed by atomic absorption spectrometry. On the other hand, emission spectra were sensitive to changes in Mn2+ concentration, showing a behavior consistent with increases in point defects such as sulfur vacancies and interstitial sulfur. It was evidenced that Mn2+ ions are presente in the ZnS structure.The last study reveals a novel supramolecular arrangement of the crystalline structure of a zinc-thiosemicarbazone complex [Zn(TPTSC)2], which exhibits potentiality as a single-source molecular precursor to ZnS nanocrystals in future works.